Single-cell genomics unveils a canonical origin of the diverse mitochondrial genomes of euglenozoans - Záhonová, Kristína; Lax, Gordon; Sinha, Savar D; Leonard, Guy; Richards, Thomas A; Lukeš, Julius; Wideman, Jeremy G (BMC biology, 2021)
BACKGROUND: The supergroup Euglenozoa unites heterotrophic flagellates from three major clades, kinetoplastids, diplonemids, and euglenids, each of which exhibits extremely divergent mitochondrial characteristics. Mitochondrial genomes (mtDNAs) of euglenids comprise multiple linear chromosomes carrying single genes, whereas mitochondrial chromosomes are circular non-catenated in diplonemids, but circular and catenated in kinetoplastids. In diplonemids and kinetoplastids, mitochondrial mRNAs require extensive and diverse editing and/or trans-splicing to produce mature transcripts. All known euglenozoan mtDNAs exhibit extremely short mitochondrial small (rns) and large (rnl) subunit rRNA genes, and absence of tRNA genes. How these features evolved from an ancestral bacteria-like circular mitochondrial genome remains unanswered. RESULTS: We sequenced and assembled 20 euglenozoan single-cell amplified genomes (SAGs). In our phylogenetic and phylogenomic analyses, three SAGs were placed within kinetoplastids, 14 within diplonemids, one (EU2) within euglenids, and two SAGs with nearly identical small subunit rRNA gene (18S) sequences (EU17/18) branched as either a basal lineage of euglenids, or as a sister to all euglenozoans. Near-complete mitochondrial genomes were identified in EU2 and EU17/18. Surprisingly, both EU2 and EU17/18 mitochondrial contigs contained multiple genes and one tRNA gene. Furthermore, EU17/18 mtDNA possessed several features unique among euglenozoans including full-length rns and rnl genes, six mitoribosomal genes, and nad11, all likely on a single chromosome. CONCLUSIONS: Our data strongly suggest that EU17/18 is an early-branching euglenozoan with numerous ancestral mitochondrial features. Collectively these data contribute to untangling the early evolution of euglenozoan mitochondria.
Keywords: Europium; Phylogeny; mitochondriální DNA; genom mitochondriální; europium; DNA, Mitochondrial; Evolution; Mitochondrial ribosome; Genome, Mitochondrial; Single-cell amplified genome; Genomics; Euglenozoa; RNA transferová; Euglenida; RNA, Transfer; fylogeneze; genomika